2005
DOI: 10.1093/carcin/bgi214
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Akt signaling and enhanced ERK1/2 activity are involved in induction of macroautophagy by triterpenoid B-group soyasaponins in colon cancer cells

Abstract: Triterpenoid B-group soyasaponins have been found to induce macroautophagy in human colon cancer cells at concentrations obtainable through consumption of legume foodstuffs. In the present studies the mechanism(s) for this autophagy-inducing action of soyasaponins was evaluated by measuring changes in signal transduction pathways associated with autophagy. Specifically, inhibition of the Akt signaling pathway and enhanced activity of ERK1/2 have previously been implicated in controlling induction of macroautop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
129
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(141 citation statements)
references
References 59 publications
9
129
2
1
Order By: Relevance
“…20,47,[71][72][73][74][75] However, similar to MAPK1/3 activation, activation of MAPK11/12/13/14 by ER stress was not affected by knockdown of RIPK1 in melanoma cells under ER stress as detected using an antibody against phosphorylated MAPK11/12/13/14 in western blot analysis, suggesting that neither MAPK1/3 nor MAPK11/12/13/14 plays a part in RIPK1-mediated induction of autophagy by ER stress (Fig. S8).…”
Section: Discussionmentioning
confidence: 85%
“…20,47,[71][72][73][74][75] However, similar to MAPK1/3 activation, activation of MAPK11/12/13/14 by ER stress was not affected by knockdown of RIPK1 in melanoma cells under ER stress as detected using an antibody against phosphorylated MAPK11/12/13/14 in western blot analysis, suggesting that neither MAPK1/3 nor MAPK11/12/13/14 plays a part in RIPK1-mediated induction of autophagy by ER stress (Fig. S8).…”
Section: Discussionmentioning
confidence: 85%
“…Another natural product, triterpenoid saponins isolated from soybeans, induces autophagy in colon cancer cells with downregulation of Akt and upregulation of ERK. 18,19 In addition, a vitamine D analog, EB1089, induces autophagy in MCF-7 cells with partially condensed chromatin; Beclin 1 overexpression sensitizes these cells to EB 1089. 20 Interestingly, silencing Beclin 1 also inhibits cell proliferation in these cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several anti-cancer agents are known to inhibit the PI3K/Akt/mTOR/p70S6K pathway, resulting in induction of autophagy in tumor cell lines [17] . In this study, we found that hyperoside treatment significantly decreased the expression levels of phospho-Akt (Ser473), phospho-mTOR, phospho-p70S6K (Thr389) and phospho-4E-BP1 (Thr37/46) in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 3D, treatment with hyperoside caused marked decreases in phosphorylated Akt in a concentration-dependent manner. In addition, increased activity of ERK1/2 has been reported to be required for induction of autophagy [17] . Therefore, we investigated whether hyperoside increases the level of phosphorylated ERK1/2, a key regulator of autophagy downstream of Akt.…”
Section: Hyperoside Induces Autophagy In A549 Cellsmentioning
confidence: 99%
See 1 more Smart Citation